Penerapan Metode Free Expression untuk Meningkatkan Kreativitas Peserta Didik dalam Pembelajaran Seni Rupa Kelas II Sekolah Dasar Negeri 165/VIII Sumber Arum Kabupaten Tebo - Putri Khoiriah; Rhesti Laila Ulfa (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to describe the application of the Free Expression method in improving the learning process and increasing students' creativity in Class II Fine Arts Learning at State Elementary School 165/VIII Sumber Arum, Tebo Regency. This type of research is Classroom Action Research. This research includes planning, implementation, observation and reflection stages. The subjects of this research were students in class II of State Elementary School 165/VIII Sumber Arum, Tebo Regency. The instruments of this research are educator observation sheets, student observation sheets, performance tests, and documentation. The data analysis technique for this research uses qualitative and quantitative analysis techniques. The results of the research are: 1. There was an increase in the learning process which can be seen from the observation sheet in Cycle I Meeting 1, namely 72.5, the value of Cycle I Meeting II, namely 80, the value of Cycle II Meeting I, namely 85, and the value of Cycle II Meeting II, namely 90. Furthermore, the value of the results of the student observation sheet for Cycle I Meeting 1, namely 70, the value of Cycle I Meeting II, namely 77.5, the value of Cycle II Meeting I, namely 85, and the value of Cycle II Meeting II, namely 92.5, (2) There has been an increase in student creativity in Fine Arts Learning which can be seen in the performance test scores. At the Pre-cycle stage the average score was 68.6 in the poor category, increasing in Cycle I, namely 78 in the Fairly Good category and increasing in Cycle II, namely 87 in the Good category. So, it can be concluded that the application of the Free Expression method can increase students' creativity in Class II Fine Arts Learning at State Elementary School 165/VIII Sumber Arum, Tebo Regency.